Germinability of seeds stored in capsules on plants of two myrtaceous shrubs: Differences among age cohorts and between species - Kim, J.; Walck, J.; Hidayati, S.; Merritt, D.; Dixon, Kingsley (2009)
Canopy-stored seed banks are a common trait among members of several plant families in sclerophyllous woodlands of Australia and South Africa, with their fruits usually opening in response to damage or fire. Unknown is whether the degree of dormancy and of germination differs among age cohorts in seeds stored on the mother plant. We examined the extent and speed of germination from two intensely serotinous myrtaceous species, Callistemon glaucus and Calothamnus quadrifidus, for seed held in capsules for up to 9 years. Germination of both species differed significantly among age cohorts (P>0.0001). However, no consistent increase in germination over a range of temperatures with storage was found, suggesting that no after-ripening occurred and that seeds were non-dormant at maturity. Differences among cohorts may be due to pre-conditioning. Significant (P=0.0214) differences occurred between the small-seeded Callistemon and the large-seeded Calothamnus. Germination was (1) optimum at <20°C for Callistemon but at <20°C for Calothamnus, (2) 912 days earlier for Callistemon than for Calothamnus, and (3) higher in light than in darkness for Callistemon but equal in both light conditions for Calothamnus. While germination of the species differed in important features, we would expect synchronous germination of all age cohorts to occur following fire and the onset of regular rainfall. © 2009 CSIRO.